2020
DOI: 10.1177/0272431620931199
|View full text |Cite
|
Sign up to set email alerts
|

Positive Youth Development and Being Bullied in Early Adolescence: A Sociocultural Analysis of National Cohort Data

Abstract: In the current study, we investigated the developmental dynamics between positive youth development, being bullied in adolescence, gender, and sociocultural risk factors. Participants were 3,509 males (49%) and 3,656 females (51%) studied longitudinally across the ages of 9, 13, and 17 years in the Growing Up in Ireland study. Using structural equation modeling, we discovered that being bullied in early adolescence was most strongly predicted by having fewer close friends, higher family poverty, and living in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 70 publications
2
24
0
Order By: Relevance
“…Focusing on specific numerical cut-offs may neglect the important features of a youth’s context. Thus far, researchers have adapted the 5Cs model to Irish (D’Urso, Symonds, & Pace, 2020) Icelandic (Gestsdóttir, Geldhof, Lerner, & Lerner, 2017), Lithuanian (Erentaitė & Raižienė, 2015), and Finnish (Ansala & Uusiautti, 2016) youth with great success. Given the similar Western European demographics and cultural context that the Scottish youth in this study represent, we believe this approach is similarly applicable to other Western democracies with homogeneous populations as long as flexible, qualitative measures are employed.…”
Section: Discussionmentioning
confidence: 99%
“…Focusing on specific numerical cut-offs may neglect the important features of a youth’s context. Thus far, researchers have adapted the 5Cs model to Irish (D’Urso, Symonds, & Pace, 2020) Icelandic (Gestsdóttir, Geldhof, Lerner, & Lerner, 2017), Lithuanian (Erentaitė & Raižienė, 2015), and Finnish (Ansala & Uusiautti, 2016) youth with great success. Given the similar Western European demographics and cultural context that the Scottish youth in this study represent, we believe this approach is similarly applicable to other Western democracies with homogeneous populations as long as flexible, qualitative measures are employed.…”
Section: Discussionmentioning
confidence: 99%
“…As the first school in a person's life, family, to a certain extent, bears the heavy responsibility. Hence, parents have become the first teacher in people's life (Haines‐Saah et al, 2018; Urso et al, 2021). The disharmony of family education is bound to be the root cause of campus bullying.…”
Section: Research Results and Analysismentioning
confidence: 99%
“…Being socially disadvantaged can also make children the object of discrimination in a culture that constructs social hierarchies based on wealth (Hosang & Bhui, 2018;Kingston & Webster, 2015). However, in an Irish national study no associations were found between parental economic wealth and the prevalence of victimisation in adolescence (D'Urso et al, 2020). Unexpectedly, attending lower income schools had a small negative impact on victimisation which was interpreted by the authors as demonstrating solidarity and close peer ties in those communities (D'Urso et al, 2020).…”
Section: Individual Characteristics Of Bullies and Victimsmentioning
confidence: 85%
“…However, in an Irish national study no associations were found between parental economic wealth and the prevalence of victimisation in adolescence (D'Urso et al, 2020). Unexpectedly, attending lower income schools had a small negative impact on victimisation which was interpreted by the authors as demonstrating solidarity and close peer ties in those communities (D'Urso et al, 2020). Possibly, other types of disadvantages (e.g., lack of care from parents, being a member of a minority group) might be more important for bullying and victimisation than family economic wealth.…”
Section: Individual Characteristics Of Bullies and Victimsmentioning
confidence: 86%
See 1 more Smart Citation